A New Pyrrole Alkaloid from Capsicum annuum L. var. palmera Grown in La Palma (Canary Islands, Spain) - Jesús G. Díaz; María A. de Buergo; David Díaz Díaz (Molbank)
Capsicum annuum, commonly known as pepper, is a widely cultivated crop valued for its nutritional and economic significance. Among its varieties, the small red bell pepper, locally known as “pimienta palmera”, is a unique cultivar from La Palma in the Canary Islands, renowned for its distinctive flavor and use in traditional dishes. Despite its cultural importance, limited research exists on the chemical composition of this pepper variety. This study investigates the chemical constituents of dichloromethane and n-butanol fractions extracted from the pericarp of Capsicum annuum var. palmera. Isolation and structural elucidation of compounds were achieved using high-resolution mass spectrometry (HREIMS), nuclear magnetic resonance spectroscopy (NMR), and chromatographic techniques. A previously unreported pyrrolo-lactone compound, 2-(6-formyl-3-oxo-3,4-dihydro-1H-pyrrolo[2,1-c][1,4]oxazin-4-yl)acetic acid, was identified alongside other metabolites, including α-tocopherol, β-sitosterol, and oleic acid. This alkaloid adds to the chemical diversity of Capsicum species and highlights the unique bioactive potential of this regional pepper. These findings enhance the understanding of pimienta palmera’s composition and suggest potential applications in nutraceuticals and pharmacology due to the biological activity associated with pyrrole alkaloids. The characterization of this compound underscores the need to further explore the phytochemical richness of traditional crops with limited prior research.